Environmental and geographic study of betanin accumulation in promising red beet accessions from the VIR collection - D. V. Sokolova (Труды по прикладной ботанике, генетике и селекции)
Background. Table beet (Beta vulgaris L.) is a source of ‘betanin’, a natural food dye known as food additive E-162. The VIR collection holds a large diversity of red beet accessions. It is the base for obtaining source material to breed cultivars with high betanin content.Materials and methods. In the framework of this study, which lasted from 2015 to 2018, a group of 29 accessions identified during the screening was analyzed. The pigment was assessed at the laboratory of the ECO RESOURCE Joint-Stock Company using Spectrophotometer SF-2000. Field experiments were performed according to VIR’s guidelines in 2015–2017 at Pushkin and Pavlovsk Laboratories of VIR, Volgograd Experiment Station of VIR, and Maikop Experiment Station of VIR.Results. Environmental and geographic tests demonstrated that the ability to accumulate the pigment was variable among the red beet accessions, and its concentrations were notably different. The research showed that accumulation of betanin is primarily associated with agroclimatic growing conditions. The dynamics of pigment accumulation can be both positive and negative. The optimal zone for growing the studied accession is Leningrad Province, where the highest content of betanin was observed. Mid-ripening and cold-resistant old landraces were a reference point in the search for the desired genotypes.Conclusion. The process of pigment accumulation is extremely responsive to weather conditions, soil water balance, and watering uniformity. The negative impact of these factors would smooth down the crop’s varietal polymorphism. Diseases and insect pests have led to slowing and stopping the accumulation of betanin. As a result of the comprehensive agroecological study of prototypes, promising accessions were identified and recommended for cultivation in Leningrad Province with the aim of betanin production.